Kekerasan Seksual Pada Perempuan Berdasarkan UU No. 12 Tahun 2022 - Dimas Gibran Satrio Utomo; Tajul Arifin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Law No. 12 of 2022 concerning the Prevention and Handling of Sexual Violence Crimes has become a significant milestone in the effort to combat sexual violence, especially against women, in Indonesia. In this context, this article explores the impact and implications of the law, as well as the challenges faced in its implementation. Through qualitative analysis of various sources of information, including the text of the law, official reports, and related literature, this article provides a comprehensive understanding of how the law affects the protection of victims of sexual violence. The results of the analysis indicate that Law No. 12 of 2022 has increased public awareness, strengthened victim protection, and marked a cultural shift towards sexual violence.